Prioritas Permasalahan Pengelolaan Keuangan Desa Pada Desa di Lubuk Pakam, Kabupaten Deli Serdang Sumatera Utara - Khrisna Fadillah Satyadira (Journal Economy and Currency Study (JECS), 2021)
Law Number 6 of 2014 mandates the Village Government to be in a position to control its funds effectively. However, in practice, village monetary management is still not effective. The reason of this find out about used to be to analyze the precedence issues in village monetary management in Lubuk Pakam, Deli Serdang Regency, North Sumatra Province. The approach used is the Analytic Network Process (ANP). The effects of the evaluation in this learn about point out that the electricity subculture is the most dominant trouble variable in village economic administration in Lubuk Pakam. In addition, based totally on the effects of the analysis, it can additionally be viewed that the variables that have a larger have an impact on are: energy sub-culture, financial sub-culture, periodic village improvement plans, well-organized regulations, social sub-culture, administration of BUMDes that is effective, as nicely as the existence of partnerships with the commercial enterprise world (private).